Beginnings of state care for mentally ill in ireland - Williamson, A (Economic & Social Studies, 1970)
The purpose in this paper is to examine the background and development of state care for the mentally ill in Ireland. Today, with a rapidly growing awareness of the needs of people with psychiatric problems, many agencies, state and voluntary, are doing excellent work; and in Ireland the recommendations of the Commission of inquiry on mental illness, published in 1966, did much to bring into focus the strength and weakness of this facet of the social services.
Keywords: Economics; Sociology